2017
DOI: 10.1101/135830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of curcumin nanoformulations on cellular function in Niemann-Pick disease type C astrocytes

Abstract: Niemann-Pick disease type C1 (NPC disease) is a neurodegenerative multi-lipid lysosomal storage disease caused by mutations in the NPC1 gene presenting with reduced lysosomal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…The nanoformulation of curcumin can be a promising agent against Niemann-Pick disease type C astrocytes [120]. Curcumin has been reported to have several medicinal properties, wherein it was observed that nanoformulations of curcumin were able to increase cytosolic calcium ion levels and cell viability in astrocytes [120]. Another compound δ-tocopherol was found to decreased cholesterol levels and also lipid accumulation, it also reduced lysosomal enlargement.…”
Section: Frontotemporal Dementia (Ftd)mentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoformulation of curcumin can be a promising agent against Niemann-Pick disease type C astrocytes [120]. Curcumin has been reported to have several medicinal properties, wherein it was observed that nanoformulations of curcumin were able to increase cytosolic calcium ion levels and cell viability in astrocytes [120]. Another compound δ-tocopherol was found to decreased cholesterol levels and also lipid accumulation, it also reduced lysosomal enlargement.…”
Section: Frontotemporal Dementia (Ftd)mentioning
confidence: 99%
“…Extracts of Piper nigrum (fruit) and Curcuma longa (rhizome) also inhibited the AChE significantly which is considered one of the key targets for therapeutic strategies against dementia [119]. The nanoformulation of curcumin can be a promising agent against Niemann-Pick disease type C astrocytes [120]. Curcumin has been reported to have several medicinal properties, wherein it was observed that nanoformulations of curcumin were able to increase cytosolic calcium ion levels and cell viability in astrocytes [120].…”
Section: Frontotemporal Dementia (Ftd)mentioning
confidence: 99%